2012
DOI: 10.1016/j.jtcvs.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide insufflation in open-chamber cardiac surgery: A double-blind, randomized clinical trial of neurocognitive effects

Abstract: Carbon dioxide pericardial insufflation in open-chamber cardiac surgery does not affect postoperative neurocognitive decline. The most important factor is atheromatous vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
0
30
1
3
Order By: Relevance
“…In addition, the elimination time of air was significantly shorter in the treatment group . The theory that carbon dioxide field flooding can eliminate air in the wound with efficiency has also been supported by other studies . As different size of embolus and local flow , only a fraction of intracardiac or intra‐aortic emboli will reach the local circulation , but they are positively correlated.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In addition, the elimination time of air was significantly shorter in the treatment group . The theory that carbon dioxide field flooding can eliminate air in the wound with efficiency has also been supported by other studies . As different size of embolus and local flow , only a fraction of intracardiac or intra‐aortic emboli will reach the local circulation , but they are positively correlated.…”
Section: Discussionmentioning
confidence: 54%
“…We identified a total of 335 citations through our search strategy. After the screen process, four articles were identified and fulfilled inclusion criteria . Details of study selection are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations